History and traditions of early Israel : studies presented to Eduard Nielsen, May 8th 1993 - Lemaire, André, 1942-; Otzen, Benedikt.; Nielsen, Eduard. (Supplements to Vetus Testamentum ;, 1993)
This book is published as a Festschrift on the occasion of the 70th birthday of professor Eduard Nielsen (Copenhagen). In accordance with the main themes of Eduard Nielsen's scholarly works the articles concentrate on the history of early Israel, id est Israel before the classical prophets in the 8th century B.C., and on literary traditions referring to this phase of Israelite history. The articles are concerned with topics in the Books of the Pentateuch, with the epoch of King David, as well as with archaeology, Canaanite traditions et cetera Eduard Nielsen's bibliography is included at the end of the book.